Effectiveness of computerised decision aids for patients with chronic diseases in shared decision‐making: A systematic review and meta‐analysis - Wu, Chih‐Jung; Yeh, Tzu‐Pei; Chu, Ginger; Ho, Ya‐Fang (Journal of clinical nursing, 2024)
Aims To synthesise the composition and effectiveness of computer‐based patient decision aid (PDAs) in interventions for patients with chronic diseases. Design A systematic review with meta‐analysis. Methods Five databases were searched, and only randomised controlled trials (RCTs)were included. This review was conducted with the PRISMA guidelines. The JBI Appraisal Tools for randomised trials were used to assess the risk of bias. We used the random‐effects model to conduct meta‐analyses. Evidence from RCTs was synthesised using standardised mean differences or mean differences. The GRADE system was employed to assess the certainty of evidence and recommendations. This study was registered on PROSPERO (number: CRD42022369340). Data Sources PubMed, Embase, Web of Science, CINAHL and Cochrane Library were searched for studies published before October 2022. Results The review included 22 studies, and most computer‐based PDAs reported information on the disease, treatment options, pros and cons and risk comparison and value clarification. The use of computer‐based PDAs showed a significant effect on decision conflict and knowledge, but not on decision regret, satisfaction, self‐efficacy, anxiety and quality of life. The overall GRADE certainty of evidence was low. Conclusion Although the quality of evidence was low, however, using computer‐based PDAs could reduce decision conflict and enhance knowledge when making medical decisions. More research is needed to support the contention above. Relevance to Clinical Practice Computer‐based PDAs could assist health‐care providers and patients in the shared decision‐making process and improving the quality of decision‐making. Reporting Method This study adhered to PRISMA guidelines. No Patient or Public Contribution